2009
DOI: 10.1146/annurev.ecolsys.110308.120320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Enemy Biodiversity on the Suppression of Arthropod Herbivores in Terrestrial Ecosystems

Abstract: Claims about the role of predator diversity in maintaining ecosystem function and providing ecosystem services such as pest control are controversial, but evaluative tests are beginning to accumulate. Empirical and experimental comparisons of species-rich versus species-poor assemblages of entomophagous arthropods and vertebrates range from strong suppression to facilitative release of herbivorous arthropod prey. Top-down control can be strengthened when natural enemies complement each other, dampened by negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
359
1
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(394 citation statements)
references
References 89 publications
13
359
1
9
Order By: Relevance
“…Root-feeding nematodes (level 3) can suppress N 2 fixation by feeding on roots and decreasing the number of root nodules for N 2 fixation [30]. Similarly, for pest control, consumptive predator activity traits (level 1) affects pest populations (level 2), which in turn affect crop yields (level 3) [61,62]. Thus, it is crucial not only to apply traits to understudied trophic levels, but also to understand the interactions among multiple trophic levels.…”
Section: Traits Across Multiple Trophic Levelsmentioning
confidence: 99%
“…Root-feeding nematodes (level 3) can suppress N 2 fixation by feeding on roots and decreasing the number of root nodules for N 2 fixation [30]. Similarly, for pest control, consumptive predator activity traits (level 1) affects pest populations (level 2), which in turn affect crop yields (level 3) [61,62]. Thus, it is crucial not only to apply traits to understudied trophic levels, but also to understand the interactions among multiple trophic levels.…”
Section: Traits Across Multiple Trophic Levelsmentioning
confidence: 99%
“…About half the time (45.6%), predator diversity enhanced predation, but predator diversity negatively influenced predation almost as frequently (40.3%), likely due to substitutable effects or interspecific interference. Letourneau et al (2009) reviewed 62 studies, yielding 266 comparisons of diverse versus non-diverse mixtures of natural enemies. Most often (69.5% of comparisons), natural enemy diversity enhanced pest suppression, but sometimes (30% of comparisons), diversity decreased pest suppression.…”
Section: Relationships Between Biodiversity and Ecosystem Servicesmentioning
confidence: 99%
“…For predators, sampling effects may occur where certain species have disproportionately large effects in a community, or where a single species has relatively greater abundance, prey capture ability, longevity, reproductive capacity, or competitive ability (Letourneau et al 2009). In biological control efforts, the sampling effect may be evident with releases of specialist species.…”
Section: Sampling or Selection Effectsmentioning
confidence: 99%
“…It has been suggested that the abundance of natural enemies of herbivores increases with greater crop biodiversity [18]. By extension, higher natural enemy species richness is strongly associated with a reduction in herbivore abundance [19]. Polycultures promote greater diversity and abundance of generalist predators by supporting a greater array of herbivores throughout different stages of the growing season [18].…”
Section: Villagementioning
confidence: 99%